Quoting Nothing - Pavone, Luigi (JoLMA)
This paper argues that the practice of employing bare pairs of quotation marks to represent the empty string in formal linguistics and computer science is well-founded in the implicit conventions governing the use of quotation marks in natural language. In the framework of the Inscriptional Theory of Quotation (ITQ), it is argued that sentences containing empty quotation (i.e., empty quotational sentences) are grammatical and meaningful. Furthermore, the notion of an empty string is employed in the analysis of reported speech to provide a unified account that identifies mixed quotation as the primary form of reported speech.